2021
DOI: 10.3390/biom11070930
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Omics Analysis of Camellia sinesis Pollen Tubes in Response to Low-Temperature and Nitric Oxide

Abstract: Nitric oxide (NO) as a momentous signal molecule participates in plant reproductive development and responds to various abiotic stresses. Here, the inhibitory effects of the NO-dominated signal network on the pollen tube growth of Camellia sinensis under low temperature (LT) were studied by microRNA (miRNA) omics analysis. The results showed that 77 and 71 differentially expressed miRNAs (DEMs) were induced by LT and NO treatment, respectively. Gene ontology (GO) analysis showed that DEM target genes related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Oxidative stress and inflammation are thought to be the groundwork of liver disease caused by factors including heavy metal accumulation, viral inflammation, alcohol, drugs, and other aspects [ 39 ]. Consistently, the current study revealed that Cd could cause oxidative stress and inflammatory damage in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation are thought to be the groundwork of liver disease caused by factors including heavy metal accumulation, viral inflammation, alcohol, drugs, and other aspects [ 39 ]. Consistently, the current study revealed that Cd could cause oxidative stress and inflammatory damage in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…With the development and popularization of omics technology, an increasing number of studies focusing on pollen grain function, including transcriptomics (Keller et al, 2018 ), proteomics (Chaturvedi et al, 2016 ; Keller et al, 2018 ), and metabolomics (Fragallah et al, 2018 ; Paupière et al, 2019 ), have been conducted in recent years. With the application of transcriptomics technology, Xu et al ( 2021 ) found that the abnormal growth of the Clonorchis sinensis pollen tube caused by NO-induced by low temperature could be due to the differential expression of miR5721, miR5819, and miR1429-3p, and novel_mir_18 regulated their target genes related to pollen tube growth, resulting in changes in insufficient energy, cell wall organization, and ion distribution for pollen tube growth, thus inhibiting polar growth of C. sinensis pollen tube tips after low-temperature treatment. Fragallah et al ( 2018 ) focused on different germination abilities from two clones of Chinese fir [ Cunningham ia lanceolata (Lamb.)…”
Section: Introductionmentioning
confidence: 99%